Ruwat sukerta: Strengthening Muslim Family Resilience Through Preserving Local Culture - Suraiya, Ratna; Jauhari, Nashrun; Wandoyo, Vierda Anggraini; Chodir, Fatkul (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2025)
The purpose of this study was to reveal the wisdom value of ruwat sukerta in the Javanese marriage tradition that still survives today. Ruwat sukerta is still believed to be able to prevent married couples from bad luck and is able to create a harmonious family. The subjects of the study were the semi-urban Muslim community in Sampangagung Village, Kutorejo, Mojokerto. The research analysis used Clifford Geertz’s symbolic interpretation theory and Zainab al-’Alwani’s Muslim family resilience theory. This field research used a qualitative approach with descriptive data presentation. The results of the study: (1) Ruwat sukerta in the Javanese Muslim community is still practiced and has shifted from traditional rites to religious ceremonies in the form of a walimah procession (a wedding celebration held after the marriage contract), wedding reception, thanksgiving and joint prayer; (2) The practice of ruwat sukerta still represents local wisdom that can encourage the realization of Muslim family resilience in strengthening the legal basis of marriage, economic resilience, psychological resilience, and socio-cultural resilience of the family.